Dasar-Dasar Pemberian Punishment - Mursal Aziz; Syarifudin Syarifudin (Al-Liqo: Jurnal Pendidikan Islam, 2020)
Punishment is a way of giving a warning to students at school by educators due to improper students' behavior so that their attitudes can change into correct and expected general norms. The purpose of this study was to find out the basics of giving punishment applied by educators. The method used was qualitative library research. Primary data sources were prioritized related to the punishment theories, then complemented by secondary sources related to the punishment problem. The results showed that the basics of giving punishment must be done to students who behave wrongly, don't overdo, the form of punishment has a relationship with miss-behavior, give punishment based on the wrong action committed, it must be consistent with the rules, be calm and objective, and before giving punishment, students should first be given a warning.